An Analysis of Performance-Based Human Resource Development among Employees at the Center for Environmental and Forestry Generation Development - Fitria Fitria; Hamsinah B Hamsinah B; Hadi Supratikta (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study examines the implementation of performance-based human resource development (HRD) at Pusat Pengembangan Generasi Lingkungan Hidup dan Kehutanan (PPGLHK), an organizational unit under the Ministry of Environment and Forestry, Indonesia. Using a qualitative descriptive design, the study involved four key informants selected through purposive sampling (the Head of the Center, two Division Heads, and the Head of the Administrative Subdivision). Data were collected through in-depth interviews, observations, focus group discussions (FGD), and supporting document analysis, and were analyzed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing). The findings indicate that performance-based HRD at PPGLHK has been oriented toward achieving organizational performance goals; however, implementation remains constrained by limited time, misalignment between certain training materials and job needs, and insufficient post-training evaluation. Program effectiveness is shaped by workload, leadership support, and the availability of facilities and infrastructure. Overall, HRD initiatives are reported to contribute positively to employee performance, particularly in terms of work quality, output quantity, and work reliability, although stronger coordination and a more comprehensive evaluation mechanism are required to better integrate HRD programs with organizational performance strategies.